2021
DOI: 10.3390/su13116076
|View full text |Cite
|
Sign up to set email alerts
|

Managing Sustainable Transitions: Institutional Innovations from India

Abstract: Despite the widespread disruptions of lives and livelihoods due to the COVID-19 pandemic, it could also be seen as a gamechanger. The post-pandemic recovery should address fundamental questions concerning our food systems. Is it possible to reset existing ecologically unsustainable production systems towards healthier and more connected systems of conscious consumers and ecologically oriented farmers? Based on three illustrative cases from different parts of India, we show how managing transitions towards sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…A recent study recommended that Farmer Producer Organisations (FPOs) can enable sustainable transitions during these covid times (Chebrolu and dutta 2021). In another study in India, it was concluded that FPO facilitates many innovative practices and helps in economic, environmental, and social benefits to the FPO.…”
Section: Role Of Collectivesmentioning
confidence: 99%
“…A recent study recommended that Farmer Producer Organisations (FPOs) can enable sustainable transitions during these covid times (Chebrolu and dutta 2021). In another study in India, it was concluded that FPO facilitates many innovative practices and helps in economic, environmental, and social benefits to the FPO.…”
Section: Role Of Collectivesmentioning
confidence: 99%
“…Transition management is about fostering sustainability transitions from a system perspective [8], where participatory, collaborative processes involving multiple actors and individuals are considered essential to reach the ultimate goal of sustainability. In fact, recent literature often presents the need for intermediary actors and organizations to navigate the fluid boundaries between adaptation and transformation in sustainable transitions [16,23,24]. Still, the framework of transition management is lacking in detail as to how organizations and individuals can in practice and prepare to engage in transition processes inside as well as outside of the organization.…”
Section: Individuals In Transition Processesmentioning
confidence: 99%
“…The risk of climate change and environmental degradation can impact their livelihoods significantly, as they continue to recognise that the input-intensive modes of agriculture, following the Green Revolution, come at high costs. With increasing evidence of the ecological footprint of agriculture the transition to sustainable agriculture is an imperative and yet public policies continue to favour industrial chemical agriculture even as agroecological alternatives exist (Kumar et al , 2021; Paul et al , 2023; Prasad and Dutta, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mignon and Kanda (2018) discussed the type of organisations that may play the role of transition intermediaries, namely, network or cluster organisations, government-funded agencies that provide resource support and project development companies or consultancies. However, in the case of agricultural and food systems transitions, an important form of organisation is the PO (Prasad and Dutta, 2021; Groot-Kormelinck et al , 2022). POs play the role of intermediaries for their members both in classic terms and in terms of sustainability transitions (Groot-Kormelinck et al , 2022).…”
Section: Introductionmentioning
confidence: 99%